SOSIALISASI MAKANAN BERGIZI DAN DAMPAKNYA TERHADAP STUNTING PADA ANAK - Abdullah, Dessy; Ade Teti Vani; Nadia Purnama Dewi; M. Fiqran Mulyadi (Nusantara Hasana Journal, 2024)
Stunting in children is a significant nutritional problem and can affect children’s long-term physical and cognitive development. The main cause of stunting is malnutrition that occurs in the first thousand days of life, which covers the period from pregnancy to two years of age. This community service program aims to increase public understanding of the importance of providing nutritious food in preventing stunting. The methods used include counseling about balanced nutrition, workshops on making nutritious food, education about exclusive breastfeeding, and providing information about appropriate nutritional supplements for children. Apart from that, educational tools and healthy food packages were also provided to strengthen the implementation of the knowledge gained, which was attended by 29 mothers and children on the south coast of the Nyalo x Koto river. The results of this program show an increase in parents’ knowledge regarding the importance of balanced nutrition, as well as changes in children’s eating patterns that are more nutritious. Evaluation through monitoring children’s nutritional status also shows improvements in the physical development of several children in the community. Thus, this program has succeeded in having a positive impact in reducing the risk of stunting and improving the quality of life for children, as well as showing the importance of collaboration between the government, medical personnel and the community in efforts to prevent stunting.